Catálogo de tecnologias para identificação de comportamentos do usuário; Suporte à avaliação de usabilidade para dispositivos médicos - Tito, Thâmmara Lariane Henriques (2018)
Currently, the medical device manufacturer (MD) and usability engineer’s deal with user unpredictability according to the subjective convenience they deem necessary for the type and MD risk classification during usability testing, for compliance purposes in the country of marketing. This research aimed to provide a Catalog of Technologies with indications of technologies and technological resources that could be used to identify behaviors or physiological or ergonomic users, from the capture of objective data that generate information on cognitive states of humans, aiming to support to the manufacturer and the team responsible for the usability test in the interface monitoring and for assistance in the usability evaluation of MD. For this, a bibliographic review was carried out on studies in which technologies were used to detect human behavior, specifically behaviors that reflect the probable cognitive state or the physical conditions of an individual, in order to select 10 technologies among the m ost used in scientific research, in the last 2 years. In the next stage, based on the selected technologies, a research was carried out in the world market in search of technological resources capable of capturing biometric and bioelectrical physiological signals, physical expressions and biomechanical movements, as well as the search for the technical information provided by the manufacturer of resources. The purpose was to compose a non-exhaustive list of technologies and their respective technological resources currently available in the market. The selected technologies resulted in: Detection of Ocular Phenomena through Eye Tracking, Detection of Motor Factors of Face Muscles for Facial Recognition, Identification of Bioelectrical Signals during Brain Activity through Electroencephalography, Identific ation of Bioelectrical Signals during Myocardial Physiological Activity by Electrocardiogram , Heart Rate Check, Identification of Electro Dermal Activity through Galvanic Skin Response Measurement, Identification of Bioelectrical Signals during Muscle Physiological Activities Through Electromyography, Force and Pressure Measurement, Capture of Interfaces Images and Capture of Body Movements, being found 53 technological resources. The Technology Catalog was assembled with descriptions of technologies followed by lists of technological resources with their respective technical information to enable manufacturers and usability engineering teams to learn about technologies available in the market and to compare among them which may possibly identify the behavior of the user that interests them during the MD usability test being evaluated. The research was completed with the delivery of the Catalog of Technologies that has information on technologies and technological resources capable of detecting physiological signals and physical expressions and generating objective data to aid the understanding of human cognitive and physical states. These data enable the identification of user behaviors and can complement subjective analysis of user unpredictability in user- centered usability testing. Therefore, the Technology Catalog is a support to the manufacturers and the usability engineering team in the usability evaluation of MD.